The relationship of the sense of coherence and distress tolerance with childbirth self-efficacy with the mediating role of body intelligence - Ahmad Esmaili; Mozaffar Ghafari; Parisa Hosseini (Shahrekord University of Medical Sciences, 2021)
Background and aims: Childbirth self-efficacy (CSE) reduces women's fear over labor and increases their tendency for vaginal delivery. The aim of this study was to evaluate the relationship of the sense of coherence (SOC) and distress tolerance (DT) with CSE with the mediating role of body intelligence (BI). Methods: This descriptive-correlational study was conducted in 2019 on 240 women aged 20-40 years who referred to primary healthcare centers in Maragheh, Iran, to receive reproductive care services. Sampling was done through multistage random sampling and data were collected using a demographic questionnaire, the Lowe's Childbirth Self-Efficacy Inventory, the Antonovsky's Sense of Coherence scale, the Simons and Gahar's Distress Tolerance Scale, and the Anderson's Body Intelligence Scale. The SPSS and the AMOS software (v. 22.0) were used for data analysis through the Pearson's correlation analysis, the Bootstrapping method, and the Sobel's test. Results: DT, SOC, and BI significantly predicted 16% of the variance of CSE. The direct effects of DT (0.20), SOC (0.15), and BI (0.20) in CSE prediction were significant (P<0.05). Moreover, the indirect effects of SOC (t=2.72) and DT (t=2.46) with the mediating role of BI were significant. Conclusion: Women's CSE can be improved through improving their SOC, DT, and BI.